Carbon dots@metal–organic frameworks as dual-functional fluorescent sensors for Fe3+ ions and nitro explosives. Issue 22 (19th May 2021) - Tao, Yufang; Jiang, Yansong; Huang, Yating; Liu, Junning; Zhang, Ping; Chen, Xiaodong; Fan, Yong; Wang, Li; Xu, Jianing
Abstract : Two novel dual-functional fluorescent composites were prepared, which exhibit excellent fluorescence sensing capabilities for Fe 3+, p -NT and 2, 4-DNP. Abstract : Carbon dots (CDs) with excellent optical properties were encapsulated into two fluorescent metal–organic frameworks (MOFs), namely, [Cd(HL)]·0.8H2 O (1 ) and [Cd3 (L)2 ]·3H2 O (2 ) (H3 L = 4-(5-carboxypyridin-2-yl)isophthalic acid). The as-prepared CDs@1 and CDs+2 not only retained the strong fluorescence activity of CDs, but also embedded Eu 3+ ions in the hybrids to form dual-emitting Eu 3+ /CDs@1 and Eu 3+ /CDs+2 . These novel composites emitted strong red light at room temperature and exhibited good fluorescence sensing capabilities for Fe 3+ ions, p -nitrotoluene ( p -NT) and 2, 4-dinitrophenol (2, 4-DNP) in water solutions with detection limits of 0.034 μM, 0.0096 μM, 0.062 μM and 0.0111 μM. These results indicate that 1A and 2A (activated products of Eu 3+ /CDs@1 and Eu 3+ /CDs+2 ) could be regarded as potential dual-functional fluorescent sensors with superior sensitivity and excellent selectivity.